The Role of the Regional Government of Tual City in Resolving Social Conflicts Between Communities in Tual City (Case Study of the Yarler Complex and the Bandaeli Complex) - Marthin Fians Renoat; Fricean Tutuarima; Marlen S Sapulette (CV. Rayyan Dwi Bharata, 2024)
This research aims to find out the policies taken by the Regional Government in resolving social conflicts in Tual City, as well as finding out the obstacles faced by the regional government in resolving social conflicts in Tual City. This research is a qualitative research with a phenomenological research type, using primary data and secondary data with several informants from the Tual City Government, residents in conflict, as well as people who saw/know about the conflict events in question. Data collection was carried out through interviews, field observations, and documentation. Meanwhile, the data analysis used in this research is qualitative descriptive to describe in detail the reality found in the field. The research results show that the factors that cause social conflict between Yarler residents and Banda Eli residents in Tual City are due to alcohol, the problem of lack of employment opportunities, the spread of hoax information via social media. Based on the results of interviews and observations at the research location, it can be concluded that in handling social conflict between residents of the Yarler complex and residents of the Banda Eli complex, the Tual City Government has handled and resolved it well, but it has not been optimal as mandated in Law Number 7 of 2012